2010
DOI: 10.1590/s0100-83582010000500005
|View full text |Cite
|
Sign up to set email alerts
|

Competição de plantas daninhas com a cultura do café em duas épocas de infestação

Abstract: RESUMO -Objetivou-se com este trabalho avaliar a interferência de plantas daninhas instaladas aos 60 e aos 180 dias após o transplantio de plantas de café em vasos contendo 25 dm 3 de substrato. O experimento foi instalado no delineamento em blocos casualizados, com quatro repetições, em esquema fatorial (2 x 4 x 2), com duas espécies de plantas daninhas (Brachiaria decumbens e Brachiaria plantaginea), cultivadas por 90 dias, em quatro densidades (zero, dois, quatro e seis plantas por vaso), juntamente com mud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 15 publications
1
12
1
3
Order By: Relevance
“…It was observed that, even if the management operations (fertilization, control of diseases, among others) are performed in the entire area, this will not result in uniformity of yield in the plantation. Yield variation is influenced by factors such as: biennuality (Camargo & Camargo, 2001); soil fertility and leaf nutrition (Wadt & Dias, 2012;Scalco et al, 2014); occurrence of pests, diseases and weeds (Fialho et al, 2011;Carvalho et al, 2012;Lopes et al, 2012), among others.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that, even if the management operations (fertilization, control of diseases, among others) are performed in the entire area, this will not result in uniformity of yield in the plantation. Yield variation is influenced by factors such as: biennuality (Camargo & Camargo, 2001); soil fertility and leaf nutrition (Wadt & Dias, 2012;Scalco et al, 2014); occurrence of pests, diseases and weeds (Fialho et al, 2011;Carvalho et al, 2012;Lopes et al, 2012), among others.…”
Section: Resultsmentioning
confidence: 99%
“…The interference of weeds on coffee plants may be more damaging in the first two years after transplanting the seedlings into fields, due to the slow initial growth of the crop compared to the weed community (Fialho et al, 2010), making interventions necessary. To do so, control performing is necessary, and it is usually carried out through cutting and chemical control between the rows and through herbicides applied by directed spraying or manual weeding in the planting line (Melloni et al, 2012).…”
Section: Resumo -As Espécies De Trapoerabamentioning
confidence: 99%
“…A presença de outras espécies, mesmo que daninhas, nas entrelinhas, pode trazer benefícios para a cultura do café, como o aumento da diversidade biológica e da proteção da superfície do solo contra a erosão (Fialho et al 2010), porém, a competição de plantas daninhas por nutrientes é um forte fator limitante ao crescimento das plantas de café, reduzindo, em até 50%, o teor de macronutrientes e, em até 41%, o desenvolvimento de cafeeiros jovens (Carvalho et al 2013). observaram 20% de perdas na produtividade de lavouras adultas.…”
Section: Occurrence Of Weeds In Coffee Intercropped With Macadamiaunclassified